Marketing Strategy Proposal for House of Dunna - Muria, Zarrah; Hariandja, Evo S (The Indonesian Journal of Business Administration, 2013)
The growth of Muslim fashion market, is affecting the increasing number of brand that sells Muslim apparels. Today, many people concern with the growth of Muslim fashion, both Muslim fashion producers and consumers. Moreover, Indonesia is planned to be one of the Muslim fashion center in the world. Many fashion businesses are seeing this as an opportunity as well as House of Dunna. House of Dunna is a new brand in Muslim fashion with it main products are party dress, and other products are daily apparel for semi-formal occasion. House of Dunna began the operations based on current STP and marketing strategy, but the profit and consumers targeted had not achieved. This condition is considered as problem for House of Dunna. Meanwhile House of Dunna already has differentiation strategies that are offered to customers as a value preposition. With these strategies, it is expected that House of Dunna be able to produce unique and qualified products compared to its competitors, it is also expected House of Dunna be able to achieve the targeted market share. The problem faced by House of Dunna can be solves by conducting internal and external factors analysis, and marketing mix analysis. The result can be used to propose the new marketing strategy and its implementation. The method that used in this research is exploratory through literature study and field research that supported by questionnaires. From the results of the research, the products that offered by House of Dunna has its own uniqueness and quality such as neatness of stitches, design qualities, and limited number of products, the offline-store is stated in a strategic location in the middle of fashion business street, but House of Dunna had not promote optimaly its products yet. Therefore, to face the tight competition in Muslim fashion, House of Dunna is needed to create a new marketing strategy, so it can be used to achieve the targets. Â Keyword: Boutique, Muslim Fashion, Marketing Strategy